PELAKSANAAN FIDUSIA SEBAGAI JAMINAN KREDIT DALAM PERSPEKTIF HUKUM BISNIS DI INDONESIA - Suparno, Perli (Journal of Law ( Jurnal Ilmu Hukum ), 2025)
ABSTRACT. The implementation of fiduciary guarantee execution faces various technical and administrative obstacles. In the event of a default, creditors often face challenges in executing the pledged object, especially if the object has changed hands or has been damaged. This research discusses the legal certainty of the implementation of fiduciary as credit guarantee in Indonesia and the obstacles faced in the implementation of fiduciary as credit guarantee from a business law perspective. This research uses normative research, in this case normative legal research is a process to find legal rules, legal principles, and legal doctrines to answer legal problems. The results of the study are that after the enactment of the Fiduciary Law and the decision of the Constitutional Court. Fiduciary registration provides legal certainty for creditors in enforcing their rights, while the Constitutional Court's ruling provides more protection for debtors in terms of the execution of guarantees and these constraints include low levels of compliance with fiduciary registration, challenges in the enforcement process, limited supervision and law enforcement, and lack of public understanding of fiduciaries. Keywords: Fiduciary, Credit Guarantee.